Electro-based technologies for contaminants removal from soil and effluent targeting further reuses - Ferreira, Ana Rita Lourinho (2018)
This work would not have been possible without the INTERREG SUDOE project 4KET4REUSE - KETs for the removal of emerging contaminants in treated wastewater from the SUDOE area (SOE1/P1/E0253, 2016 – 2019) that funded most of it, which I deeply acknowledge. The Department of Civil Engineering from the Technical University of Denmark (DTU) is also acknowledged for the funding of the study of the arsenic and petroleum hydrocarbons removal from soil. This work has also received funding from the European Union’s Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No. 778045, the IDS-FunMat-INNO Doctoral Programme funded by the KIC EIT-Raw Materials, the Portuguese Polar Programme-PROPOLAR, the Erasmus+ scholarship, which all were a great contribution to carry out this work.